Demographic pattern, clinical features and treatment outcome of patients with infective keratitis in the eastern region of Nepal - Lavaju, P; Arya, SK; Khanal, B; Amatya, R; Patel, S (Nepalese Journal of Ophthalmology, 2010)
Background: Corneal ulcer is one of the major causes of monocular blindness in developing countries. Objective: To determine demographic pattern, risk factors, microbiological pattern and treatment outcome of infective keratitis. Materials and methods: A retrospective analysis of hospital records of 44 patients with clinically-diagnosed infective keratitis presenting to B.P. Koirala Institute of Health Sciences in the eastern region of Nepal was carried out. Outcome measures: The parameters studied were risk factors and organisms responsible for keratitis. Results: The infective keratitis was mostly prevalent among the males between 21-40 years of age (50%). 79.5 % of them were engaged in agricultural work. A history of corneal injury was found in 30 eyes (68.1%). Vegetative matter was the most common agent of trauma in 17 (56.6%). Culture positivity for microorganisms was observed in 20 (45.5%) samples. Of these, 8 (40%) patients had purely bacterial corneal ulcer. Purely fungal growth was seen in 4 (20%) and mixed in 8 (40%). Staphylococcus aureus was the most commonly isolated bacteria (70%). The other bacteria included Pseudomonas species, E. coli and Acinetobactor. Aspergillus species was the most common fungal organism isolated in 8 (40%) samples. 65.9 % of the patients improved with medical treatment alone. Perforation, endophthalmitis and panophthalmitis were the common complications encountered in 11.3%, 4.5% and 4.5% respectively. Conclusion: Corneal ulcer is prevalent in males, predominantly amongst the farmers. Ocular trauma with vegetative matter is the commonest predisposing factor. Staphylococcus aureus and Aspergillus species are the most commonly isolated organisms in corneal ulcers. Keywords: corneal ulcer; fungal keratitis; ocular trauma DOI: 10.3126/nepjoph.v1i2.3683 Nep J Oph 2009;1(2):101-106